2010
DOI: 10.1542/peds.2009-3412
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Candidiasis: Epidemiology, Risk Factors, and Clinical Judgment

Abstract: OBJECTIVE-Invasive candidiasis is a leading cause of infection-related morbidity and mortality in extremely low-birth-weight (<1000 g) infants. We quantify risk factors predicting infection in high-risk premature infants and compare clinical judgment with a prediction model of invasive candidiasis. METHODS-The study involved a prospective observational cohort of infants <1000 g birth weight at 19 centers of the NICHD Neonatal Research Network. At each sepsis evaluation, clinical information was recorded, cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
228
3
13

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(258 citation statements)
references
References 21 publications
14
228
3
13
Order By: Relevance
“…8,10 Notably, the site of this study has a low incidence by internal measure (3% for birth weight under 1000 grams); thus, fungal prophylaxis would not be indicated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,10 Notably, the site of this study has a low incidence by internal measure (3% for birth weight under 1000 grams); thus, fungal prophylaxis would not be indicated.…”
Section: Discussionmentioning
confidence: 99%
“…A single center retrospective study with historical controls did note a reduction in mortality after adopting an institutional guideline for initiating antifungal therapy. 9 Benjamin et al 10 identified the following as risk factors for the development of invasive candidiasis: vaginal delivery, lower gestational age at delivery, Candida dermatitis, presence of a central catheter, lack of enteral feeds, increased blood glucose, increased number of antibiotic days and decreased platelet count. From the present study, utilization of a clinical prediction modelFas discussed by Benjamin et al 10 Fcould have resulted in five of the six persistent candidemia patients receiving empiric antifungal therapy, as they had at least three of the risk factors above.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merkezlere göre invaziv kandidiyazis (İK) sıklığı değişken olmakla beraber Candida türleri ÇDDA bebeklerde kan akım enfeksiyonunun nedenleri içinde sıklık sırasına göre üçüncü sıradadır (9). ÇDDA bebeklerde antifungal tedavilere rağmen kandidaya bağlı mortalite %30 ve yaşayanlarda nörogelişimsel bozukluk %59-73 gibi yüksek oranlardadır (9)(10)(11)(12). Ayrıca, İK'i olan prematüre bebeklerde periventriküler lökomalazi (PVL), prematüre retinopatisi (PR) ve bronkopulmoner displazi (BPD) gelişme olasılığı daha yüksektir (11,12).…”
Section: Kandidaunclassified
“…(3) ICI are severe, and ICI-related mortality is still unacceptably high (up to 30%, compared with some 77% for invasive fungal infections caused by Aspergillus spp.). (4) Contrary to other high-risk patients, in preterm neonates the risk condition for fungal and Candida infections is destined to vanish as days of stay in the NICU go by. Availability of mother's fresh milk, and ability of the neonate to tolerate it as he gets older, is critical since maternal fresh milk provides innate defenses that may be helpful to overcome the risky time-window.…”
Section: Introduction the Background On Neonatal Invasive Candida Infmentioning
confidence: 99%